CONTINUOS ONLINE AUDITING DAN CONTINUOUS ASSURANCE : EVOLUSI JASA AUDIT MASA MENDATANG - ., Ariston; Handoko, Jesica (Jurnal Widya Manajemen & Akuntansi, 2006)
The advent of computer has affected numerous aspects of accounting and auditing. Computerassisted auditing has became commonplace, leading to a significant increase in efficiency of auditing (Kogan dkk., 1999). This improvements enabled management and reporting (internal and external) of finer information sets at progressively narrower time frames. This article describes continuous online auditing and continuous assurance as emerging future audit services evolution. They have three important aspects in implications to broaden our knowledge that online real-time information will become stakeholders’ need which auditors must be responsible as well.